Effects of rock types and crushing mechanism on the 3D morphological parameters of manufactured sands: a combination study of 3D scanning and spherical harmonic analysis - Qiu, Peiyun; Wang, Huaizhi; Wang, Peng; Xiao, Min; Wei, Jiangxiong (Frontiers in Built Environment, 2024)
This study aims to investigate the effect of rock types, i.e., granite, conglomerate rock, limestone, and crushing mechanism, i.e., Vertical Shaft Impact (VSI) crusher, Horizontal Shaft Impact (HSI) crusher, on the morphology of manufactured sands. By combining the 3D scanning and spherical harmonic analysis, the morphological parameters of manufactured sands such as elongation ratio (EL), flatness ratio (Fl), aspect ratio (AR), edge angle (EA), sphericity (SH), and fractal dimension were quantified. The results indicate limestone is more readily broken into blade-shaped particles without being able to blunt sharp edges through constant abrasion. The proportion of bladed particles in manufactured sand prepared from limestone is 1.91 times higher than the proportion of bladed particles in conglomerates. Additionally, the HSI crusher has a more significant effect on rocks with smaller strength. For the same parent rock, manufactured sand from a VSI crusher contains 30% more spherical and oblate particles than from an HSI crusher.